2021
DOI: 10.1155/2021/6634253
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of lncRNA GAS5 Contribute to Susceptibility of Ischemic Stroke among Southern Chinese Population

Abstract: Emerging evidence suggests that the long noncoding RNA (lncRNA) growth arrest special 5 (GAS5) plays crucial roles in the pathogenesis of ischemic stroke (IS). The current research is aimed at assessing the correlation between two functional GAS5 variants (rs145204276 and rs55829688) and susceptibility to IS in a Han Chinese population. This study genotyped the two GAS5 variants in 1086 IS patients as well as 1045 age-matched healthy controls by using an improved multitemperature ligase detection reaction (iML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Stroke has become the most common cause of death in China [1] of which IS accounts for the vast majority, reaching 70% to 80% [2]. At present, the effective treatment methods for IS are mainly to open arteries and restore blood flow as soon as possible [3,4] including intravenous thrombolysis and mechanical clot thrombectomy. However, due to the limitation of effective treatment time and other conditions, the vast majority of IS patients fail to receive these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke has become the most common cause of death in China [1] of which IS accounts for the vast majority, reaching 70% to 80% [2]. At present, the effective treatment methods for IS are mainly to open arteries and restore blood flow as soon as possible [3,4] including intravenous thrombolysis and mechanical clot thrombectomy. However, due to the limitation of effective treatment time and other conditions, the vast majority of IS patients fail to receive these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Other SNPs in GAS5 have been previously linked to AIS risk, like a correlation between rs145204276 del allele and increased AIS risk among a Chinese population. 32 Similarly, rs2067079 has been reported to influence lncRNA GAS5 expression level in multiple sclerosis (MS) patients with rs2067079 TT genotype. 15 However, the current study showed no similar effect of rs2067079 on lncRNA GAS5 expression which could be attributed to the relatively small sample size and the different clinical subtypes of AIS that the subjects had.…”
Section: Discussionmentioning
confidence: 99%
“…GAS5 increased in the blood of stroke patients where it was associated with increased stroke risk and poor rehabilitative outcomes in hypertensive, diabetic, and aged stroke patients. 127,128…”
Section: Epigenetic Mechanisms In Strokementioning
confidence: 99%
“…GAS5 increased in the blood of stroke patients where it was associated with increased stroke risk and poor rehabilitative outcomes in hypertensive, diabetic, and aged stroke patients. 127,128 The lncRNA maternally expressed gene 3 (MEG3) was upregulated in the core, but downregulated in the penumbra following transient MCAO in rodents. 129,130 MEG3 has been shown to play a role in the recruitment of EZH2 and the PRC2 component jumonji and AT-rich interaction domain containing 2 (JARID2) and histone H3 methylation.…”
Section: Long Noncoding Rnas As Epigenetic Regulators In Strokementioning
confidence: 99%